Storage-induced changes in β-strand interactions within bovine lactoferrin powder analyzed through X-ray diffraction - Takumi Mitsudome (Food Chemistry Advances)
Bovine lactoferrin (bLF) is a multifunctional protein used in the food and pharmaceutical industries. Various commercially available bLF powders (bLFPs) have different ratios of protein monomers to aggregates, which affects the aggregation rate. However, the changes in molecular structure and interactions during aggregation are unclear. This study investigated changes in the structure and interactions of stored bLFPs during aggregation. Five commercially available bLFPs with different molecular weight distributions were analyzed before and after storage using size-exclusion chromatography and X-ray diffraction (XRD) to monitor aggregation and β-strand interaction, respectively. These bLFPs were stored for four weeks under high temperature and humidity conditions as a stress test. The XRD results revealed changes in peak II (around 2θ = 20°), corresponding to β-strand interactions. The peak II change rate suggested that the aggregation occurs due to partial structural fluctuations and interaction changes. Furthermore, time-course analysis of peak II and correlations with the pre-storage monomer ratio and aggregation phase index demonstrated that β-strand interactions decreased during the transformation of monomers to low-molecular-weight (LMW) aggregates, while it increased during the LMW-to-high-molecular-weight aggregate phase. These results provide novel insights into the conformational changes and molecular interactions of bLFPs during aggregation.